Publisher Correction: Functional characterization of Schistosoma mansoni fucosyltransferases in Nicotiana benthamiana plants - Kim van Noort; Dieu‑Linh Nguyen; Verena Kriechbaumer; Chris Hawes; Cornelis H. Hokke; Arjen Schots; Ruud H. P. Wilbers (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.